Persepsi Dokter Praktik Swasta terhadap Sistem Pelaporan Kasus Tuberkulosis di Kota Pontianak Tahun 2020: Penelitian - Alifah Fahiratunnisa, Namira; Fitriangga, Agus; Raharjo, Raharjo (Cermin Dunia Kedokteran, 2025)
Introduction: In reality, many tuberculosis (TB) patients don’t receive proper treatment. One contributing factor is the high number of unreported tuberculosis cases. This study aims to understand the perception of independent practice doctors regarding tuberculosis case reporting in Pontianak City in 2020. Method: This research uses a qualitative approach with a case study design. The research sample consists of 12 independent practice doctors from each district in Pontianak City, as well as TB program managers. The sample was determined using purposive sampling technique, and qualitative data were analyzed using content analysis. Results: The study results indicate a lack of knowledge and understanding in the private sector regarding the Minister of Health Regulation Number 67 of 2016 related to the case reporting system. Conclusion: Key factors in the underreporting of TB cases to independent practitioners include public health centers serving as the primary referral for TB patients. Additionally, there is limited knowledge and understanding of the Minister of Health Regulation Number 67 of 2016 and its implementation, a lack of coordination and socialization from the government, both directly and indirectly, to general practitioner, and uncooperative patients in TB case management.